Introduction to the cellular and molecular biology of cancer - Knowles, Margaret A. (Oxford University Press, 2005)
. What is cancer?, L.M. Franks and Margaret A. Knowles. 2. The causes of cancer, Naomi Allen, Robert Newton, Amy Berrington de Gonzalez, Jane Green, Emily Banks, and Timothy J. Key. 3. Inherited Susceptibility to Cancer, D. Timothy Bishop. 4. DNA Repair and Cancer, Beate Koberle, John P. Wittschieben, and Richard D. Wood. 5. Epigenetic Events in Cancer, Jonathan C. Cheng and Peter A. Jones. 6. Molecular Cytogenetics of Cancer, Denise. Sheer and Janet Shipley. 7. Oncogenes, Margaret A. Knowles. 8. Tumour suppressor genes, Sonia Lain and David P. Lane. 9. The cancer cell cycle, Chris J. Norbury.